1963
DOI: 10.2466/pms.1963.17.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Overlearning and Reversal of a Spatial Discrimination by Rats

Abstract: Rats were trained to criterion on a position discrimination and then given reversal training with or without 150 trials of overlearning ( N = 14). Initial reversal performance nras significantly retarded by overlearning but mean number of rrials to reversal criterion was not significantly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In fact, experiments following Reid's initial demonstration presented a more complex picture (see [34] for review). While some learning studies replicated the ORE [48], others found no effect of overtraining on reversal [49] and some found that overtraining did indeed slow reversal [50]. Such mixed results highlighted the critical dependence of the ORE on factors such as the size of reward and criterion of learning [51].…”
Section: The Overtraining Reversal Effectmentioning
confidence: 99%
“…In fact, experiments following Reid's initial demonstration presented a more complex picture (see [34] for review). While some learning studies replicated the ORE [48], others found no effect of overtraining on reversal [49] and some found that overtraining did indeed slow reversal [50]. Such mixed results highlighted the critical dependence of the ORE on factors such as the size of reward and criterion of learning [51].…”
Section: The Overtraining Reversal Effectmentioning
confidence: 99%
“…access to food. But Clayton (1963) used 10-sec. access to food in a spatial study and found no ORE; while Mackintosh (1965b), also using 10-sec.…”
Section: Reward Size and Frustrationmentioning
confidence: 99%
“…Nine of these agreed with the general correlation in the simulations, in that slow original learning led to an ORE, while fast original learning led to the opposite of an ORE (Brookshire, Warren, & Ball, 1961;Bruner, Handler, O'Dowd, & Wallach, 1958;Hill & Spear, 1963;Komaki, 1961;Mackintosh, 1962Mackintosh, , 1963aPubols, 1956;Reid, 1953;Williams, 1942). Five experiments did not support the correlation (Clayton, 1963;D'Amato & Jagoda, 1961D'Amato & Schiff, 1964;Erlebacher, 1963). In addition, eight other experiments offer support to the simulation on ORE, although their designs make the interpretation somewhat more uncertain than for those previously cited (Capaldi, 1963;Hill, Spear, & Clayton, 1962;Ison & Birch, 1961;Mackintosh, 1963bMackintosh, , 1965North & Clayton, 1959;Theios & Blosser, 1965;Wike, Blocher, & Knowles, 1963).…”
Section: Resultsmentioning
confidence: 60%